2019
DOI: 10.1136/bmjopen-2018-027970
|View full text |Cite
|
Sign up to set email alerts
|

Association between predialysis hypermagnesaemia and morbidity of uraemic restless legs syndrome in maintenance haemodialysis patients: a retrospective observational study in Zhejiang, China

Abstract: ObjectiveThe aim of the present study was to determine whether the predialysis serum magnesium level was associated with morbidity of uraemic restless legs syndrome (RLS) in maintenance haemodialysis patients.DesignA retrospective observational study of morbidity of uraemic RLS was conducted.SettingPatients on maintenance haemodialysis three times a week.ParticipantsWe reviewed 578 patients receiving maintenance haemodialysis for >1 year as our cohort.Outcome measuresUraemic RLS was diagnosed according to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In contrast, a prospective case-control questionnaire study for RLS involving 600 pregnant women showed a significantly higher magnesium intake in patients with RLS than in those without RLS [ 39 ]. In addition, a recent retrospective study involving 578 ESRD patients receiving maintenance haemodialysis for more than 1 year has shown an association of pre-dialysis hypermagnesemia both with uraemic RLS and with increased morbidity of this syndrome [ 40 ]. The results of these studies [ 39 , 40 ] are along the same lines as our finding of increased serum magnesium levels in patients with iRLS (none of the women included in our study were pregnant) in comparison with controls.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a prospective case-control questionnaire study for RLS involving 600 pregnant women showed a significantly higher magnesium intake in patients with RLS than in those without RLS [ 39 ]. In addition, a recent retrospective study involving 578 ESRD patients receiving maintenance haemodialysis for more than 1 year has shown an association of pre-dialysis hypermagnesemia both with uraemic RLS and with increased morbidity of this syndrome [ 40 ]. The results of these studies [ 39 , 40 ] are along the same lines as our finding of increased serum magnesium levels in patients with iRLS (none of the women included in our study were pregnant) in comparison with controls.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38] Some studies have found that the length of the dialysis period may determine RLS occurrence. [39][40][41] Yang et al 42 showed that predialysis hypermagnesaemia might be an independent risk factor for RLS. The mean age of ESRD patients appears to have no association with the presence of RLS.…”
Section: Epidemiology Of Rls In Patients With Dialysismentioning
confidence: 99%
“…Moreover, HD -related RLS is associated with a variety of physical and psychological disorders, such as insomnia, fatigue, anxiety, and depression, which seriously affect patients' prognosis and quality of life and even lead to an increased risk of cardiovascular events and death (Mousavi et al, 2021;Stergiannis et al, 2020;Tuncel et al, 2011Tuncel et al, , 2019Tsai et al, 2019;Yang et al, 2019;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients on HD are more vulnerable to RLS due to ferritin loss and changes in phosphate and parathyroid hormone levels, suggesting that HD is a significant risk factor for RLS (Huzmeli et al., 2018; Ramachandran et al., 2018). Moreover, HD ‐related RLS is associated with a variety of physical and psychological disorders, such as insomnia, fatigue, anxiety, and depression, which seriously affect patients’ prognosis and quality of life and even lead to an increased risk of cardiovascular events and death (Mousavi et al., 2021; Stergiannis et al., 2020; Tuncel et al., 2011, 2019; Tsai et al., 2019; Yang et al., 2019; Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%